2019
DOI: 10.1061/(asce)em.1943-7889.0001660
|View full text |Cite
|
Sign up to set email alerts
|

Dependency of Dilatancy Ratio on Fabric Anisotropy in Granular Materials

Abstract: The relationship between dilatancy and anisotropy is a fundamental aspect of anisotropic behavior of granular materials. Existing test data directly investigating this relationship are scarce and conflicting. Discrete element biaxial and triaxial numerical tests on idealized granular materials in both two-dimensional (2D) and three-dimensional (3D) are conducted in this study to acquire high quality stress, strain, dilatancy, and fabric data for various anisotropic samples, which are utilized to analyze the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…For the five fabric anisotropy‐related parameters || F nin ||, Δ 1 , Δ 2 , c 2, and c 3 , calibration should ideally be conducted based on measurements of fabric anisotropy under conventional triaxial loading on specimens with different initial fabric anisotropy. This is easily achieved when the fabric tensor can be directly measured, such as in DEM numerical tests, which has been exhibited in two recent works 27,29 . However, although technology for direct measurement of fabric is being developed for laboratory tests, 76,77 such measurements are still not easily achievable.…”
Section: Model Formulation Unifying the Effects Of Principal Stress Vmentioning
confidence: 99%
See 2 more Smart Citations
“…For the five fabric anisotropy‐related parameters || F nin ||, Δ 1 , Δ 2 , c 2, and c 3 , calibration should ideally be conducted based on measurements of fabric anisotropy under conventional triaxial loading on specimens with different initial fabric anisotropy. This is easily achieved when the fabric tensor can be directly measured, such as in DEM numerical tests, which has been exhibited in two recent works 27,29 . However, although technology for direct measurement of fabric is being developed for laboratory tests, 76,77 such measurements are still not easily achievable.…”
Section: Model Formulation Unifying the Effects Of Principal Stress Vmentioning
confidence: 99%
“…DEM numerical tests on virtual granular materials offer a convenient alternative. Though DEM test results may differ quantitatively from their physical world counterparts, studies have shown that the qualitative behavior patterns of sand can be reproduced for monotonic loading, 27,29,30 cyclic loading, 85,86 and PSAR 7,8,40,66 . Xue et al 8 proposed a 3D force‐line method to apply arbitrary stress boundary conditions on DEM specimens that allows for the application of any 3D stress paths, which enables simulations with principal stress axes rotating in any arbitrary plane as is in engineering reality.…”
Section: Model Performance For Dem Numerical Tests Under 3d Psarmentioning
confidence: 99%
See 1 more Smart Citation
“…The microstructure includes the arrangement of particles, voids and interparticle contacts. This microstructure has a significant influence on the behaviour of granular soils, in particular on the shear strength and dilatancy, as has been shown by experiments [2][3][4], micromechanical studies [5][6][7][8][9][10][11][12][13][14][15] and Discrete Element Method (as proposed in [16]; DEM for short) simulations [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…induced anisotropy). Fabric anisotropy and its evolution may exert significant effects on the strength and deformation properties of discrete granular materials [1,4,17,[22][23][24], for example, the shear strength [20,[25][26][27], elastic moduli [28], non-coaxial plastic flow [29][30][31][32] and dilatancy [10,[33][34][35]. These behaviours of granular materials are closely associated with the stability and buckling of force chains at a mesoscopic scale and sliding and rolling at contacts, thus governed by the grain-scale structural characteristics and processes.…”
Section: Introductionmentioning
confidence: 99%